As protagonistas nas séries brasileiras : mulheres e figurinos que contam histórias - Collovini, Mariane Leite (2023)
This dissertation presents a study on the female representations of protagonists of brazilian television in the period from 1979 to 2019. To this end, the theoretical basis presented here works with a genealogy of Brazilian television series according to Foucault’s definition, in the studies of gender in audiovisual by Laura Mulvey and Smith, the definitions of costume as the second skin by Patrice Pavis and of clothing as discourse symbol by Castilho. The theoretical arguments serve the use of exploratory research methodology through data obtained in bibliographic searches. The study is based on gender studies of the same period and has film analysis as a methodological strategy. The objective of the research was to verify evidence that the feminist waves were related to the different typologies of female characters that appeared in the mentioned period and that they can be verified through the costumes that characterize them. To this end, a gallery of female protagonists of TV series was created, along with their respective costumes on stage. Through this analysis, it was possible to obtain a deeper understanding of the female models disseminated in Brazilian society in each moment in time. In this way, it was feasible to understand how the Brazilian audiovisual industry has contributed to a symbolic cultural change and in the perspective of the country's social.